Design and maintenance at public toilet / Ahmad Akmal Ahmad Dahlan - Ahmad Dahlan, Ahmad Akmal (2006)
Unfortunately, without talking about the problems of the public toilet it becomes harder to clearly identify the issues and provide the appropriate design solutions. This paper is examining the specific problems of the public toilet and the way in which design is addressing these problems. Public toilet have a few functional problems that have not been properly addressed. The issue of cleanliness and hygiene has been the concern of humankind for a few centuries. It seems that during the past century cleanliness and hygiene have been experienced visually. In the early 20th century hygiene became an aesthetic, which society adopted as the means for evaluating the level of cleanliness of the space. However, this is relevant to the perceived cleanliness and not necessarily to the actual level of hygiene .Another problem seems to be the lack of consideration to the gender identity of the user. The binary division into male/female restrooms is based on biological gender and not gender identity. The design of the semi public male restroom assumes that a man is willing to freely expose his penis in front of other men. Urinal phobia is not being taken into account in the design of the space. This latest trend is making use of creative forward thinking, which is based on better understanding of the user needs. Although this trend does not directly address the problems of the public toilet, it helps to create a unique experience for the visitor of the space. It appears that design today has a better understanding of the requirements of male users of the public toilet.